Nrf2 Signaling Pathway Mediates the Protective Effects of Daphnetin Against D-Galactose Induced-Premature Ovarian Failure - Zhang, Mengwen; Yu, Xiaowei; Li, Danjie; Ma, Ning; Wei, Zhentong; Ci, Xinxin; Zhang, Songling (Frontiers in Pharmacology, 2022)
Oxidative damage can lead to severe ovarian dysfunctions and even premature ovarian failure. Nrf2, a significant transcription factor that regulates the oxidative stress response of cells, declines with age. Daphnetin, as a kind of natural Chinese herbal medicine, can activate Nrf2 and further promote the antioxidant defense of cells. However, whether Daphnetin treatment can protect ovary from premature ovarian failure and the specific mechanism involved are not understood. This study aimed to investigate the protective function of Daphnetin against the ovarian aging induced by D-galactose in wild-type and Nrf2-/- mice. Female C57BL/6 mice with Wild-type and Nrf2-/- were divided into five groups separately and the premature ovarian failure model were established by D-galactose (600 mg/kg/d) through subcutaneous injection and then Daphnetin (15 and 30 mg/kg/d) were given via intraperitoneal injection and VE (30 mg/kg/d) were given by oral administration for treatment. After 42 days, ovaries tissue and serum were collected for biochemical determination, H&E staining, Immunohistochemical staining and western blot analysis. In the WT-POF group, ovarian function was broke, and the expression of the ovarian senescence-associated protein P16 and the level of oxidative stress were significantly increased, while the expression of the anti-senescence protein klotho was significantly decreased. In addition, the expression of Nrf2 and the antioxidases GCLC, HO-1 and NQO1 were decreased, but TXNIP and NLRP3 were significantly increased. Furthermore, the characteristics of premature ovarian failure were more significant in Nrf2 knockout mice than in wild-type mice, especially the expression of NLRP3 and TXNIP, suggesting that Nrf2 protects against POF by mediating the expression of NLRP3 and TXNIP. Moreover, daphnetin, an Nrf2 activator, rescued d-gal-induced POF in a dose-dependent manner, while the protective effect was weakened or even lost in Nrf2 knockout mice, which further confirmed the above assumption. Our results suggested that daphnetin is likely to be a candidate drug for premature ovarian failure treatment and it is mostly possible referred to the molecular mechanism of increasing Nrf2 expression and inhibiting NLRP3 activation in the ovarian aging process.